Analysis of financial soundness of manufacturing companies in Indonesia Stock Exchange - Widi Hidayat (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to provide information to the issuer and Bapepam and Indonesian Institute of Accountants with additional important information content of ratings and financial soundness of the indicators that do not harm investors. This is an explanatory and descriptive nature of causality using quantitative methods, using all companies listed on the Indonesia Stock Exchange (ISE) taken as the sample. The data were analyzed using discriminant statistical analysis tools are processed with SPSS. The results showed that the level of financial soundness of the manufacturing industries listed on the ISE such as 23 (62%) Companies Current Asset Growth (CAG) is low as well as Fixed Asset growth (FAG) 28 (76%) companies is still low, Equity Growth (EqG) by 27 (73%) the company, Revenue growth (RG) 27 (65%) companies and Net Income Growth (NIG) 35 (95%) firms. Two manufacturing companies have a very high NIG, thus, NIG average is very high. The seven models of financial soundness were tested based on the growth of corporate finance such as CAG, FAG, LG, EqG, RG, ExG and NIG. Only one model is not significant, the model RG, while the other model is a significant, with a significant difference be-tween the growths rates of the sound and unsound corporate finances industry groups.